Neoadjuvant nivolumab and cabozantinib in advanced renal cell carcinoma in a horseshoe kidney – how to achieve a safe and radical resection? a case report and review of the literature - Zemankova, Anezka; Studentova, Hana; Kopova, Andrea; Tichy, Tomas; Student, Vladimir; Melichar, Bohuslav (Frontiers in Oncology, 2023)
Introduction: Neoadjuvant nivolumab and cabozantinib in locally advanced renal cell carcinoma in horseshoe kidney is a novel therapeutic approach in the preoperative setting. Methods: We report a case of a 52- year old male who presented with a large inoperable tumor of the horseshoe kidney and achieved major partial radiologic response after neoadjuvant therapy with nivolumab and cabozantinib leading to radical resection of the tumor. The patient remains tumor free on the subsequent follow-up and his renal function is only mildly decreased. The systemic treatment was complicated by hepatotoxicity leading to early nivolumab withdrawal. Results: Currently, the combination therapy based on immune checkpoint inhibitors and tyrosine kinase inhibitors represents the treatment of choice in treatment-naïve patients with metastatic renal cell carcinoma in any prognostic group. The neoadjuvant treatment approach is being tested in prospective clinical trials and results are eagerly awaited. Renal cell carcinoma in a horseshoe kidney is an uncommon finding that is always challenging. Additionally, management guidance in this patient population is lacking. In some patients neoadjuvant therapy could be the only way to preserve kidney function. The initial treatment strategy should be individualized to patient needs aiming at the radical resection of the primary tumor as the only chance of getting the tumor under control in the long term. Conclusion: Herein, we highlight the feasibility of neoadjuvant systemic therapy with nivolumab and cabozantinib allowing the subsequent performance of radical tumor resection with negative margins in a patient with advanced renal cell carcinoma in a horseshoe kidney, removing the primary tumor while sparing the patient from lifelong dialysis_